Persepsi Generasi Z Terhadap Pembelajaran Bahasa Arab di MI - Sapri Sapri; Amanda Malika Nasution; Dewi Chairunnisa Siregar; Farrah Adli Shakila; Muthia Fadilaturrizqi; Rahma Alia; Sania Mar'i Adnanda Harahap; Taufik Hidayat Siregar (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research discusses the opinions of Generation Z or what we know as Gen-Z regarding Arabic language learning at MI level. The many benefits of Arabic make Arabic a mandatory subject in several institutions. This research uses library research or bibliographic research by examining several references to assess Arabic language learning in MI based on the Gen Z perspective. Literature searches were carried out by collecting references from several previous studies. The aim of this research is to explore perspectives or perceptions regarding the importance of Arabic in Early Level institutions. The results of this research are that Gen-z believes that Arabic should be taught at MI/SDI as a unique subject that differentiates MI/SDI from other state elementary schools. Generation Z needs to learn Arabic from an early age to achieve better learning outcomes.